Answer:
<u>The simplest radical form of this mathematical expression is - 3√3</u>
Step-by-step explanation:
1. Let's write in a mathematical expression the information given:
-4 the square root of 12 + the square root of 75
-4 (√12) + √75
-4 (√4 * 3) + (√25 * 3) (12 = 4 * 3 and 75 = 25 * 3)
-4 (2 √3) + 5 √3
-8 √3 + 5√3
- 3 √3
The result is- 3 square root of 3.
<u>The simplest radical form of this mathematical expression is - 3√3</u>
Answer:
A . x=13 is the solution of this question.
9514 1404 393
Answer:
102
Step-by-step explanation:
The total of ratio units is ...
6 + 3 + 8 = 17
The difference between the Charlie's ratio units and Adrian's ratio units is ...
8 - 6 = 2
That is, the total number of ratio units is 17/2 = 8.5 times that difference.
The actual difference is 12 sweets, so the total number of sweets is ...
8.5 × 12 = 102 . . . . total sweets
11x-2
You combine same so
4x-1x =3x
3x +8x= 11x
11x-2
Answer:
( intransitive) To tend steadily upward or downward. ...
( transitive) To form with a slope; to give an oblique or slanting direction to; to incline or slant. ...
( colloquial, usually followed by a preposition)
Step-by-step explanation: